Differential Europe: Domestic actors and their role in shaping spatial planning systems. - Stead, Dominic; Cotella, Giancarlo (TH Zürich, NSL, 2011)
Der einleitende Beitrag des Heftes skizziert den Hintergrund für die Wahl des Workshop-Themas "Differential Europe", dessen Ergebnisse auch das Schwerpunktthema der disp-Ausgabe bilden und Beiträge über Finnland, Griechenland, Italien, Portugal und Lettland enthält, die die nationalen Planungssysteme porträtieren und die Rolle der inländischer Akteure vor dem Hintergrund der durch die europäische Raumplanung in Gang gesetzten konvergierenden Prozesse untersuchten. Die Einleitung umreißt den möglichen Beitrag akteurszentrierter Ansätze bei die Erklärung der Widerstandsfähigkeit nationaler Systeme der Raumplanung gegenüber dem europäischen Harmonisierungsdruck.

Spatial planning systems across Europe are very diverse and reflect local policymaking styles and cultures as well as specific territorial conditions and priorities. Reforms to these planning systems are commonplace: few remain totally unchanged for long periods of time. Since most reforms to planning systems are in response to common issues and challenges facing many, if not all, planning systems, it might easily be assumed that they are leading towards a gradual convergence of spatial planning objectives, tools and/or procedures. However, the situation is more complex since reforms, and the local outcomes of reforms, are also shaped by local and national circumstances. This paper examines the potential contribution of actor-centered institutionalist approaches in explaining how spatial planning systems can retain a very specific nature and form despite experiencing common forces of change and pressures for harmonization.
Keywords: Raumplanung; Planungssystem; Planungsorganisation; Raumplanungsbehörde; Raumplanungsinstitution; Regionalpolitik; Planungsinstrument; Planungskonzept; Planungspraxis; Raumplanungspolitik; Europäisierung; Planungskultur; Raumplanungshoheit; Raumentwicklungspolitik; Raumplanungsprogramm; Akteur; Akteursforschung; Konvergenz; Harmonisierung; Territoriale Agenda der EU; Institutionenforschung; Politikforschung; Territoriale Governance; Governance; Planungsgeschichte; Planungskonzept